Experimental study of aeroacoustic noise production through combined flow measurements and array signal processing - Garcia Pedroche, Miguel (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2013)
The underlying processes behind sound generation in turbulent flows are still a source of debate. The investigation presented in this thesis focuses on the experimental approaches that aim to clarify this issue by estimating the direct correlation between simultaneous flow-acoustic observations. Under the assumption of a Lighthill type source distribution, these experimental approaches attempt to quantify the contribution that turbulence measured in a small section of turbulent flow has at an observer's location in the acoustic field. However, it has been argued that the contribution that a small section of the flow has on the overall sound measured at an observer's location could be insignificantly small due to the presence of the large number of separate source mechanisms within the flow.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin.